Non-volatile, Li-doped ion gel electrolytes for flexible WO3-based electrochromic devices. (15th January 2019) - Yun, Tae Yong; Li, Xinlin; Bae, Jaehyun; Kim, Se Hyun; Moon, Hong Chul
Abstract: Flexible electrochromic devices (ECDs) based on Li-doped ion gels and tungsten trioxide (WO3 ) are demonstrated. Colored ECDs cannot be produced using conventional ion gels comprised of copolymers and room temperature ionic liquids (RTILs) due to a lack of cations that can be inserted into WO3 . Based on considerations of the coloration mechanism, we developed Li-doped ion gels and applied these to devices. The effects of Li salt concentration are systematically examined, with respect to device dynamics, coloration efficiency, and transmittance contrast. In addition, the coloration/bleaching switching stability of the ECD produced using optimal Li salt content is investigated. The ECD exhibits distinct colored and bleached states even after 24 h operation in air. Using the described Li-doped ion gel electrolytes, flexible WO3 ECDs were successfully demonstrated with good bending stability and no electrolyte leakage. Graphical abstract: Highlights: Non-volatile, Li-doped ion gel electrolytes are designed for flexible WO3 -based ECDs. ECDs exhibit low voltage operation (–0.9 V) and large transmittance contrast ( 85%) between colored and bleached states. Electrolyte leakage is not observed in flexible ECDs containing Li-doped gel electrolyte when bending deformation is applied. Flexible ECDs maintain 90.3 and 84.5% of initial optical transmittance and coloration efficiency after 1000 bending tests.